2018
DOI: 10.1080/17457300.2018.1467461
|View full text |Cite
|
Sign up to set email alerts
|

Ability of crime, demographic and business data to forecast areas of increased violence

Abstract: Identifying geographic areas and time periods of increased violence is of considerable importance in prevention planning. This study compared the performance of multiple data sources to prospectively forecast areas of increased interpersonal violence. We used 2011-2014 data from a large metropolitan county on interpersonal violence (homicide, assault, rape and robbery) and forecasted violence at the level of census block-groups and over a one-month moving time window. Inputs to a Random Forest model included h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
0
17
2
Order By: Relevance
“…Public health agencies have the authority to receive protected health information and are the ideal partners for receiving, processing and aggregating data from multiple sources. Summary information in the form of aggregate maps and lists of businesses experiencing high counts of violence can then be shared with the community safety partnership for injury prevention and control activities 5 23 24. The Cardiff Model collects, aggregates and shares violence-related injury data, potentially through a public health agency, in a form that may be used by LE and other partners.…”
Section: Discussionmentioning
confidence: 99%
“…Public health agencies have the authority to receive protected health information and are the ideal partners for receiving, processing and aggregating data from multiple sources. Summary information in the form of aggregate maps and lists of businesses experiencing high counts of violence can then be shared with the community safety partnership for injury prevention and control activities 5 23 24. The Cardiff Model collects, aggregates and shares violence-related injury data, potentially through a public health agency, in a form that may be used by LE and other partners.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown spatial clustering of homicides to be associated with higher rates of segregation, poverty, and economic disparity (17,18). Another study found that historic crime data and demographic data reflecting poverty were best able to predict future violent crime (19).…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach emphasizing collaboration with the DEA allowed for early recognition of the recent fentanyl epidemic in Maryland and timely implementation of public health interventions (22). Although several studies have evaluated crime outcomes using mapping techniques (18,19,21,23,24), the current study highlights how the effects of a unique societal sentinel event such as the death of Freddie Gray are particularly well suited to in‐depth analysis by GIS.…”
Section: Discussionmentioning
confidence: 99%
“…1 Current law enforcement decision-making and resource allocation use predictive geographical models created exclusively from law enforcement data. 2 Advancements in model predictive accuracy have enabled more robust discussions around community violence than were possible with hotspot mapping alone. However, significant limitations of solely relying on law enforcement data remain since datasets are incomplete and do not accurately represent community violence due to underreporting of violent crimes.…”
Section: Background and Significancementioning
confidence: 99%
“… 25 Hospital acquired data may also assess effectiveness of interventions and allow for direct targeting of community areas with high violence rates. 2 18 ED data collection, therefore, is valuable and versatile for current violence prevention initiatives.…”
Section: Background and Significancementioning
confidence: 99%